Sharing Stories, Sharing Bias: How Descriptions of Context Shape Negative Stereotype Use in Response to Accounts of Economic Adversity. (29th January 2020) - Hunzaker, M B Fallin; Mann, Marcus
Abstract: Research shows that observers use negative stereotypes to construe victims of misfortune as responsible for their own fate. In two experiments, we test three situational characteristics' (injustice, scale, and control) effects on observers' tendency to use negative stereotypes when communicating stories about others' economic hardship. Study 1 examines predictions, based on social psychological theories of equity and justice, that stereotype use should increase in response to accounts of misfortune that are the result of unjust under-reward. Contrary to predictions, Study 1 found that participants used more stereotypes when retelling accounts in which the protagonist's misfortune was not the result of unjust rewards. Study 2 investigates competing predictions to Study 1, based on research regarding how portrayals of scale (whether the misfortune affects one vs. many) and control (whether another actor has control over the misfortune of another) affect perceptions of misfortune. Study 2 results indicate that stereotype use increases in response to accounts of large-scale, uncontrollable misfortune. Together, these studies suggest that qualities of portrayals (such as scale and control) are crucial in understanding stereotype transmission processes above and beyond the role of perceptions of injustice (i.e., the unequal distribution of rewards).